Soal Matematika Berbasis Higher Order Thinking Skills (HOTS) : Studi Pengembangan Dengan Fokus Pada Permasalahan Sampah - Maratul Hamidah; Alhaq, Arini; Farida, Farida (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This research develops mathematics questions based on Higher Order Thinking Skills (HOTS) specifically designed to enhance students' higher-order thinking abilities through the context of waste problems. The purpose of this research is to develop HOTS-based mathematics questions within the context of waste issues. This study employs the Research and Development method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The development stage involves nine validators, consisting of subject matter experts, question experts, and media experts. The implementation stage involves 38 students divided into two groups. Validity, reliability, distinguishing power, and difficulty level of the mathematics questions are tested by having students work on the developed HOTS questions. The assessment of the practicality of the mathematics questions based on HOTS is conducted through student response questionnaires. The validation results from the nine validators indicate criteria of